Long‐term retinoblastoma follow‐up with or without general anaesthesia. Issue 2 (4th September 2013) - Batra, Ruchika; Abbott, Joseph; Jenkinson, Helen; Ainsworth, John R.; Cole, Trevor; Parulekar, Manoj V.; Kearns, Pamela
Abstract Background Children with treated retinoblastoma undergo frequent examinations to monitor for recurrent or new tumours. Examinations under anaesthesia allow a more complete examination in younger children, however they are stressful for the family, subject the child to medical risk and consume resources. The risk of recurrent or new tumours declines with age and it is common practice to examine older children without general anaesthesia. There are no studies on the safety and cost effectiveness of this practice, or guidelines on when examination without anaesthesia (EWA) can be safely commenced. Procedure Retrospective case note review of 128 sequential patients treated for retinoblastoma in a national referral centre over 10 years. Results Following exclusions, 113 eyes of 84 children were analysed. The mean age at diagnosis was 20 months (range birth to 71 months). There were 55 unilateral and 29 bilateral cases. The mean follow‐up was 77.7 months (range 12–178 months). EWA was commenced at a mean age of 53 months (range 12–98 months). The age of conversion to EWA was largely dependent on child cooperation and disease activity. Tumour activity was detected on EWA in one child at the age of 86 months, 9 months after the last active treatment and treated successfully. Conclusions Examination without general anaesthesia does not appear to expose children to an increased risk of undetected tumour growth. This study highlights the important factors to be considered when deciding a safe time to commence EWA. Pediatr Blood Cancer 2014;61:260–264. © 2013 Wiley Periodicals, Inc.